Eucalyptol Ameliorates Dysfunction of Actin Cytoskeleton Formation and Focal Adhesion Assembly in Glucose‐Loaded Podocytes and Diabetic Kidney. Issue 22 (15th September 2019) - Kim, Dong Yeon; Kang, Min‐Kyung; Kim, Yun‐Ho; Lee, Eun‐Jung; Oh, Hyeongjoo; Kim, Soo‐Il; Oh, Su Yeon; Kang, Young‐Hee
Abstract : Scope: Podocytes are a component of glomerular filtration barrier with interdigitating foot processes. The podocyte function depends on the dynamics of actin cytoskeletal and focal adhesion crucial for foot process structure. This study investigates the renoprotective effects of eucalyptol on the F‐actin cytoskeleton formation and focal adhesion assembly in glucose‐loaded podocytes and diabetic kidneys. Methods and results: Eucalyptol at 1–20 µm reverses the reduction of cellular level of F‐actin, ezrin, cortactin, and Arp2/3 in 33 mm glucose‐loaded mouse podocytes, and oral administration of 10 mg kg –1 eucalyptol elevates tissue levels of actin cytoskeletal proteins reduced in db/db mouse kidneys. Eucalyptol inhibits podocyte morphological changes, showing F‐actin cytoskeleton formation in cortical regions and agminated F‐actin along the cell periphery. Eucalyptol induces focal adhesion proteins of paxillin, vinculin, talin1, FAK, and Src in glucose‐exposed podocytes and diabetic kidneys. Additionally, GTP‐binding Rac1, Cdc42, Rho A, and ROCK are upregulated in glucose‐stimulated podocytes and diabetic kidneys, which is attenuated by supplying eucalyptol. Rho A gene depletion partially diminishes GSK3β induction of podocytes by glucose. Conclusion: Eucalyptol ameliorates F‐actin cytoskeleton formation and focal adhesion assembly through blockade of the Rho signaling pathway, entailing partial involvement of GSK3β, which may inhibit barrier dysfunction of podocytes and resultant proteinuria. Abstract : A naturally occurring eucalyptol ameliorates F‐actin cytoskeleton formation and focal adhesion assembly, leading to inhibition of podocyte loss and foot process effacement in glomeruli. Eucalyptol blocks the Rho signaling pathway, entailing partial involvement of GSK3β, which may inhibit barrier dysfunction of podocytes and resultant proteinuria.